COMPARATIVE EFFECTS OF BORIC ACID AND RESVERATROL ON MCF-7 BREAST CANCER CELLS METASTATIC BEHAVIOUR - ALADAĞ, Tuğçe; FIRAT, Fatma (International Journal of Research -GRANTHAALAYAH, 2022)
Motivation/Background:The metastasis of tumor cells consists of steps such as epithelial-mesenchymal transition, transendothelial migration and the formation of metastatic colonization. E-Cadherin and vimentin are main proteins associated with EMT, whereas MMP-9 is associated with migration. Method:We aimed to investigate effects boric acid and resveratrol comparatively on metaatatic behaviors on MCF-7. 30μM boric acid and 50μM resveratrol were administered to BA, BA+RES, and RES groups 48hours. Cells stained immunocytochemically by Anti-E-Cadherin, Anti-Vimentin, and Anti-MMP-9 antibodies and H-Score analysis carried out and migration analyzed by woundhealing, morphologically. Results andConclusions:It’s been observed that boric acid doesn’t affect the EMT capability of the MCF-7 cells in terms of E-Cadherin and vimentin expression; whereas, it’s affect migration both by decreasing the MMP-9 expression and also by inhibiting migration.